In-situ Thermal Reduction of Graphene Oxide/alkylamine for Reinforced Polybutylene Succinate Nanocomposite - Anis Sakinah, Zainal Abidin; Kamal, Yusoh; Saidatul Shima, Jamari; Abu, Hannifa; Zulhelmi, Ismail (2017)
Biodegradable polybutylene succinate (PBS) was incorporated with graphene oxide/octadecylamine (GOODA) via simultaneous in-situ reduction and functionalization of GOODA in PBS matrix. Functionalization of graphene oxide with octadecylamine prevented aggregation and resulted in homogeneous dispersion of GOODA in PBS nanocomposite as shown in FESEM result. GOODA did not profoundly affect the crystallinity of the thermally treated PBS/GOODA nanocomposite but interestingly improved the mechanical and thermal properties. With the addition of low loading GOODA content, a sharp increase in tensile strength and Young’s modulus were observed exhibiting an increment of up to 78% and 96% from pristine PBS at 0.3wt% GOODA loading. The improvement in strength could be attributed to the successful interfacial interaction between amine group from GOODA and carboxylic group of PBS chain tail via nucleophilic substitution reaction. This improved interphase structure through in-situ reduction technique enhanced the reinforcement effect of GOODA in PBS matrix without utilizing any hazardous reducing agent.